The Relationship Between Dietary Patterns And Physical Activity With The Occurrence Of Menarche In Adolescent Girls At SMP Negeri 1 Paciran Lamongan: Hubungan Pola Makan Dan Aktivitas Fisik Dengan Kejadian Menarche Pada Remaja Putri SMP Negeri 1 Paciran - Dewi, Silvana Anggita; Nur Cholila (Journal of Health Management, Administration and Public Health Policies, 2024)
Menarche is the first sign of menstruation that marks the beginning of puberty in adolescent girls, marked by a complex hormonal process involving the hypothalamus, pituitary, and ovaries. This study aims to analyze the relationship between diet and physical activity with the incidence of menarche in adolescent girls at SMP Negeri 1 Paciran Lamongan. The research design used was correlational analytic with a cross-sectional approach. The results showed that adolescent girls with excessive diet patterns tended to experience early menarche compared to those who had sufficient diet patterns. While adolescent girls with low physical activity patterns tended to experience early menarche compared to those with moderate levels of physical activity. This study confirms that diet and physical activity are significantly related to the incidence of menarche. Therefore, it is important to improve education about balanced diet patterns and sufficient physical activity in school and family environments to support healthy puberty development. Keywords: Menarche, Physical Activity, Diet